Art and palace politics in early modern Japan, 1580s-1680s - Lillehoj, Elizabeth (Japanese visual culture, 2011)
Magnificent art and architecture created for the emperor with the financial support of powerful warlords at the beginning of Japan's early modern era (1580s-1680s) testify to the continued cultural and ideological significance of the imperial family. Works created in this context are discussed in this groundbreaking study, with over 100 illustrations in color.